Suicide Risk Factors and Prevention - Vinall, Phil (MD Conference Express, 2009)
Mental disorders, past suicide attempts, symptomatic precursors, genetic factors, sociodemographics, and environmental factors have been shown to play a role in suicide. Mental illness is the number 1 risk factor for suicide, and psychological autopsies and interviews with family members and caregivers after a suicide have shown that 90% of victims of suicide have 1 or more mental disorders at the time of death [Harris & Barraclough. Br J Psychiatry 1997]. This article discusses possible risk factors and suicide prevention strategies.